The Resolution of the Russian League Against Epilepsy Working Group Meeting (September 25, 2021, Moscow) - article Editorial (Эпилепсия и пароксизмальные состояния)
On September 25, 2021, the Russian League Against Epilepsy (RLAE) Working Group Meeting was held regarding approaches to therapy of pediatric focal epilepsy. Considering the experience of the world medical community and Russian epileptologists, the participants discussed issues related to administering diverse anti-epilepsy agents in this patient cohort. It was noted that an ideal therapy might provide rapid and long-lasting seizure control, few side effects, low potential of drug interaction, good compliance and adherence to therapy, and no effects on course of comorbidities. The article presents the Resolution of the RLAE Working Group Meeting that was approved after discussion.